Public Trust: Indonesian Policy in Developing a New Capital City (IKN) - Rifaid, Rifaid; Rachman, M. Taufik; Baharuddin, Tawakkal; Gohwong, Srirath (Universitas Muhammadiyah Yogyakarta, 2023)
Many researchers have studied public trust to assess a government policy. Trust is the key to synergizing or connecting the state, government, and society. It is an essential foundation for the state in implementing a policy. That prompted this study to research current policies on developing new capital cities (IKN) by relating them to the level of public trust. This study used a qualitative approach with descriptive content analysis. The research object was seen from Twitter users in discussing policies regarding the development of a new capital city. Sources of data obtained from the overall results of discussions about IKN. The analysis tool relied on Nvivo 12 Plus. The findings indicated that the public trusted government policies to develop IKN. Positive trust was influenced by the idea of developing IKN, which was predicted to become an example of a world city; IKN could influence economic equality, promote well-being or prosperity, and other influential factors, such as Joko Widodo's leadership as President of Indonesia. Some factors influenced the decline in public trust, concerns about environmental damage and budget problems. It is considered that the urgency of public trust in policy issues related to IKN will affect the sustainability of the IKN development plan in the future.